Les femmes, l’environnement et le développement durable - Braidotti, Rosi; Charkiewicz, Ewa; Häusler, Sabine; Wieringa, Saskia (Genre, mouvements populaires urbains et environnement, 2007)
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; discours dominant; environnement; histoire et politique; inégalités; patriarcat; projet charge mentale; périodes historiques; racisme; ressource en ligne; santé; systèmes d'oppressions; thématiques; écoféminisme

WACK!: art and the feminist revolution - Butler, Cornelia H.; Mark, Lisa Gabrielle; Museum of Contemporary Art (Los Angeles, Calif); Butler, Cornelia H.; Mark, Lisa Gabrielle; Museum of Contemporary Art (Los Angeles, Calif) (Museum of Contemporary Art, 2007)
Groundbreaking art from a revolutionary era, featuring work by more than 120 international artists, from Louise Bourgeois and Yoko Ono to Martha Rosler, Marina Abramović, and Cindy Sherman. There had never been art like the art produced by women artists in the 1970s, and there has never been a book with the ambition and scope of this one about that groundbreaking era. WACK! documents and illustrates the impact of the feminist revolution on art made between 1965 and 1980, featuring pioneering and influential works by artists who came of age during that period, Chantal Akerman, Lynda Benglis, Theresa Hak Kyung Cha, Valie Export, Mary Heilmann, Sanja Iveković, Ana Mendieta, Annette Messager, and others, as well as important works made in those years by artists whose careers were already well established, including Louise Bourgeois, Judy Chicago, Sheila Levrant de Bretteville, Lucy Lippard, Alice Neel, and Yoko Ono. The art surveyed in WACK! includes work by more than 120 artists, in all media, from painting and sculpture to photography, film, installation, and video, arranged not by chronology but by theme: Abstraction, "Autophotography," Body as Medium, Family Stories, Gender Performance, Knowledge as Power, Making Art History, and others. WACK!, which accompanies the first international museum exhibition to showcase feminist art from this revolutionary era, contains more than 400 color images. Highlights include the figurative paintings of Joan Semmel; the performance and film collaborations of Sally Potter and Rose English; the untitled film stills of Cindy Sherman; and the large-scale, craft-based sculptures of Magdalena Abakanowicz. Written entries on each artist offer key biographical and descriptive information and accompanying essays by leading critics, art historians, and scholars offer new perspectives on feminist art practice. The topics, including the relationship between American and European feminism, feminism and New York abstraction, and mapping a global feminism, provide a broad social context for the artworks themselves. WACK! is both a definitive visual record and a long-awaited history of one of the most important artistic movements of the twentieth century. Essays by: Cornelia Butler, Judith Russi Kirshner, Catherine Lord, Marsha Meskimmon, Richard Meyer, Helen Molesworth, Peggy Phelan, Nelly Richard, Valerie Smith, Abigail Solomon-Godeau, Jenni Sorkin Artists include: Marina Abramović, Chantal Akerman, Lynda Benglis, Dara Birnbaum, Louise Bourgeois, Judy Chicago, Lygia Clark, Jay DeFeo, Mary Beth Edelson, Valie Export, Barbara Hammer, Susan Hiller, Joan Jonas, Mary Kelly, Maria Lassnig, Linda Montano, Alice Neel, Senga Nengudi, Lorraine O'Grady, Pauline Oliveros, Yoko Ono, Orlan, Howardena Pindell, Yvonne Rainer, Faith Ringgold, Ketty La Rocca, Ulrike Rosenbach, Martha Rosler, Betye Saar, Miriam Schapiro, Carolee Schneemann, Cindy Sherman, Hannah Wilke
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; arts; arts visuels et médiatiques; corps; cours; discipline; femmes* artistes; har4600; histoire et politique; premier cycle; périodes historiques; thématiques

Le patriarcat ou le féminisme noir - Charlery, Hélène (Revue française d’études américaines, 2007)
Les travaux actuels parus sur le féminisme et la population noire aux États-Unis insistent fréquemment sur l’attitude des Africaines-Américaines à l’égard de l’idéologie féministe (Terrelonge ; Roth). Peu d’études en revanche ont été consacrées aux prises de position des hommes et des dirigeants noirs sur la question. D’après les analyses récentes, une majorité d’Africains-Américains, hommes et femmes, redouterait que le féminisme ne divise les genres au sein du groupe, qu’il n’écarte les Noirs de leur priorité dans la lutte contre la discrimination raciale ou encore qu’il n’engendre un débat médiatique sur la sexualité des Africains-Américains. À ces raisons, Pauline Terrelonge ajoute l’héritage du nationalisme noir de la seconde moitié des années 1960 (Terrelonge 563). On constate aussitôt que les prises de positions citées précédemment sont liées à l’histoire des Noirs aux États-Unis et de leur stigmatisation dans les discours dominants. Pour les Africains-Américains, le féminisme imposerait alors une confrontation entre la race et le genre, bien que les féministes noires aient toujours envisagé de prendre en compte « l’intersectionalité » des deux notions .
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; afro-féminisme; amériques; approches et analyses; cours; discipline; féminisme afroaméricain; histoire et politique; intersectionnalité; masculinité; patriarcat; pol5185; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; états-unis

Théorie queer et cultures populaires: de Foucault à Cronenberg - De Lauretis, Teresa ("Le genre du monde", 2007)
Littérature, cinéma, sémiotique, psychanalyse, étude sur le genre, féminisme queer, depuis les années 1980, Teresa de Lauretis, universitaire italienne enseignant au Etats-Unis, porte une pensée critique au travers de tous ce champs. Elle relit Freud à partir des épistémologies lesbienne et gaie, en lui empruntant ses théories du fantasme et de la pulsion. Elle revisite Gramsci Foucault ou Althusser, s'appropriant, croisant et hybridant les apports, construisant une conception du sujet de part en part social et psychique. Ce premier recueil de textes publié en français par Pascale Molinier et traduit par Sam (M.H) Bourcie tente de rassembler plusieurs aspects fondamentaux de sa pensée. Dans Technologie de genre Teresa de Lauretis montre comment le genre est construit comme représentation par " des technologies sociales, des appareils techno-sociaux ou biomédicaux " et en même temps subjectivé par chaque individu. Avec "Théorie queer: sexualités lesbiennes et gaies" apparaissait en 1990 la première occurrence du terme a Queer Theory dans le domaine des études sur le genre. Enfin, dans " Culture populaire, fantasmes public et privé ", prenant pour objet le film de David Cronenberg, "M. Butterfly "", elle confronte l'effet des formes culturelles populaires à celui des fantasmes privés. Attentif au sexuel comme énigme, à la culture comme force sociale, le travail de Teresa de Lauretis, toujours au plus près de sa propre expérience, excède souvent son objet pour éclairer l'ensemble des représentations et des rapports sociaux qui nous construisent comme individus.
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; com5170; cours; culture populaire; cycles supérieurs; discipline; fem1000; fem7000; har4600; identités LGBTQIA2+; incontournable; lit2815; lit3220; lit3495; phi2030; premier cycle; périodes historiques; queer; rapports sociaux de sexe; régions géographiques; sciences humaines; soc2014; technologie; thématiques; violences; épistémologie; états-unis

Esquisse d'une épistémologie de la théorisation féministe en art - Dumont, Fabienne; Sofio, Séverine (Cahiers du Genre, 2007)
Résumé Les recherches dans et sur le domaine de la théorisation féministe en art étant peu développées en France, nous avons choisi de revenir, dans cet article, sur les contextes d’émergence de cette théorisation, depuis les premières réflexions sur la place des femmes dans le monde artistique jusqu’aux tentatives d’articuler pratiques esthétiques et expression politique, sous l’influence du mouvement féministe. Dans un second temps, nous tentons d’établir une typologie des thématiques que les questionnements féministes ont contribué à renouveler tant dans le domaine de l’art que, plus largement, dans celui de la réflexion sur la création artistique, des années 1980 à aujourd’hui.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; sex1911; thématiques; théorie de l'art; épistémologies féministes

Fonction sexuelle masculine et sexualité féminine - Giami, Alain (Communications, 2007)
Major changes have occurred in male and female sexual function/dysfunction research and treatments. Male erectile dysfunction has been re-conceptualized as an organic dysfunction, which marks a dramatic shift from previous conceptions of psychogenic impotence developed during the 60' and the 70's. This shift is based on major scientific discoveries, and pharmacological advances that took place since the early 80's under the influence of North American urologists. The release of sildenafil in 1998 was thecorner stone of a new paradigm of treatments focusing on male penile activity, far remote from any psychological approaches. More recently, the same group of urologists started to reconsider Female Sexual Dysfunction using the same organic/biological model of sexual function. New pharmaceutical products are currently under trial for the treatment of this new category of female sexual disorder. But as opposed to the absence of public adverse reaction to the development of this approach of male function, many voices raised to oppose this new conception of female function. A major discussion took place in the British Medical Journal (2003) stating that female sexual function was not organically driven, but rather determined by the social, psychological and interpersonal context of female sexual activity and relations. One of the major dimension of this discussion opposed the so-called "simplicity" of male sexual function to the "complexity" of female sexual function.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 2000 à aujourd'hui; 2000-2009; angleterre; approches et analyses; cours; discipline; essentialisme; europe; féminisme radical; patriarcat; premier cycle; pédagogie; périodes historiques; recherche; régions géographiques; santé; sciences humaines; sexisme; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques

Gabriel Girard – Interview Elsa Dorlin : Le Queer est un matérialisme - Girard, Gabriel (Syllepse, 2007)
Interview d'Elsa Dorlin pour l'ouvrage "Femmes, genre, féminismes".
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; amériques; approches et analyses; cours; discipline; europe; france; féminisme matérialiste; histoire et politique; philosophie; philosophie politique; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; soc2014; thématiques; états-unis

Queer Theory and Sociology: Locating the Subject and the Self in Sexuality Studies - Isaiah Green, Adam (Sociological Theory, 2007)
In this paper, I revisit the relationship of queer theory and sociology in order to address some critical issues around conceiving the subject and the self in sexualities research. I suggest that while sociology and queer theory are not reducible to each other, sociology has its own deconstructionist impulse built into pragmatist and symbolic interactionist analyses of identity and subjectivity that is often overlooked by or reinvented through queer theory. But, conversely, queer theory has a very specific deconstructionist raison d'etre with regard to conceiving the sexual subject that marks its key departure from Foucault and sociology more generally. This deconstructionist mandate, by definition, moves queer theory away from the analysis of self and subject position—including those accruing from race, class and gender—and toward a conception of the self radically disarticulated from the social. This “anti-identitarian” position has been a source of criticism among some sociologists who find in queer theory an indefensible “refusal to name a subject” ( Seidman 1993:132). But this criticism, I suggest, stems from a misplaced effort to synthesize queer theory and sociology when, in fact, the two approaches to the subject are founded on incommensurable methodological and epistemological principles. Rather, I argue that the very promise of queer theory rests in a strong deconstructionism that exists in tension with, rather than as an extension of, sociological approaches to the self
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; cours; discipline; méthodologie; premier cycle; périodes historiques; queer; sciences humaines; soc2014; sociologie; thématiques